2010
DOI: 10.1016/j.molcel.2010.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Pathways Generate MicroRNA-like RNAs and Dicer-Independent Small Interfering RNAs in Fungi

Abstract: A variety of small RNAs, including the Dicer-dependent miRNAs and the Dicer-independent Piwi-interacting RNAs, associate with Argonaute family proteins to regulate gene expression in diverse cellular processes. These two species of small RNA have not been found in fungi. Here, by analyzing small RNA associated with the Neurospora Argonaute protein QDE-2, we show that diverse pathways generate miRNA-like small RNAs (milRNAs) and Dicer-independent small interfering RNAs (disiRNAs) in this filamentous fungus. Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
425
2
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(460 citation statements)
references
References 47 publications
24
425
2
9
Order By: Relevance
“…The Neurospora crassa Argonaute protein QDE-2 (Nc QDE-2) is a close sequence homolog of eukaryotic AGOs that act in the small interfering RNA (siRNA) and miR-NA pathways [e.g., sequence identities with Hs AGO2 and Dm AGO1 are 30% and 29.7%, respectively (Fig. S1) (22,23)]. We obtained diffracting crystals of a QDE-2 fragment containing the MID and PIWI domains (amino acids 506-938) and determined the structure at 3.65 Å resolution (crystal form I; Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Neurospora crassa Argonaute protein QDE-2 (Nc QDE-2) is a close sequence homolog of eukaryotic AGOs that act in the small interfering RNA (siRNA) and miR-NA pathways [e.g., sequence identities with Hs AGO2 and Dm AGO1 are 30% and 29.7%, respectively (Fig. S1) (22,23)]. We obtained diffracting crystals of a QDE-2 fragment containing the MID and PIWI domains (amino acids 506-938) and determined the structure at 3.65 Å resolution (crystal form I; Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the contribution of the PIWI domain to 5′-nucleotide binding in vitro, we used size exclusion chromatography. As a substrate, we chose a 10-mer guide RNA mimic that started with a 5′-phosphorylated uridine (23). We first showed that the MID domain alone could not bind the substrate (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with their ability to mediate a cancer-specific function, MRPL3 is overexpressed in nonsmall cell lung cancers (14) and MALAT1 in non-small cell lung cancers and hepatocellular carcinomas (15, 16). Although we have not examined the mechanism by which these genes promote metastasis, MRPL3 promotes the translation of mRNAs encoding mitochondrial enzymes (17) and the biogenesis of miRNA-like small RNAs (miRNAs) (18), and MALAT1 is involved in alternative splicing (19) and transcriptional activation of growth-control genes (20). These results indicate that a gain-of-function cDNA screen in a mouse model of mammary-tumor progression enables the identification of single genes implicated in lung colonization.…”
Section: Significancementioning
confidence: 97%
“…The investigators hypothesized that the observed burst of rDNA-related qiRNAs inhibits protein translation as a response to DNA damage. MicroRNA-like RNAs (milRNAs) and Dicer-independent small interfering RNAs (disiRNAs) have also been reported (Lee et al 2010b). milRNAs are produced by at least four different mechanisms that use a distinct combination of factors, including Dicers, QDE-2, the exonuclease QIP, and an RNase III-like domain-containing protein, MRPL3.…”
Section: Quellingmentioning
confidence: 99%
“…milRNAs are produced by at least four different mechanisms that use a distinct combination of factors, including Dicers, QDE-2, the exonuclease QIP, and an RNase III-like domain-containing protein, MRPL3. In contrast, disiRNAs do not require the known RNAi components as they originate from loci producing overlapping sense and antisense transcripts (Lee et al 2010b). Notably, it was observed that the product of qde-1, QDE-1, has DNA-and RNA-dependent biochemical activities (Lee et al 2010a).…”
Section: Quellingmentioning
confidence: 99%